Airport design and operation - Kazda, Antonín, 1952- (Elsevier, 2007)
The annual number of airline passengers has continued to increase in the past decade, putting great strain on the airports. Increasing volumes of passengers and freight will continue making demands for expansion of airport facilities and construction of new airports. Traditionally airport design and airport operation have been treated separately, yet they are closely related and influence each other. Poor design adversely affects operation; sound understanding of operation is needed to enable good design. The aim of this book is to present a new and integrated approach to the two. This second.
Previous edition: Amsterdam; Oxford: Pergamon, 2000.
Keywords: Airports -- Design and construction.; Airports -- Planning.; Airports -- Management.; elektronické knihy; electronic books